TEACHING ENGLISH THROUGH POEM - Faisal Rahman (UIN Alauddin Makassar, 2018)
This is a conceptional article which the writer proposes a concept of teaching English trhough Poem. The integrated of literature in language teaching is very important. The most widely used language in the world is English, there are many people need to learn English for communication. There are several ways of teaching English, one of them is through literature that is a part of a language, the use of literature in English language teaching can be as authentic material. There are many literary works that can be used for teaching English, one of them is the poem.Hypothetically, the use of poem in English language teaching can help the teacher improve the students’ English language skills and knowledge about the culture of the nation of English. In a class, a teacher should be creative and give the opportunity for students to use English actively and understanding the poem content.